2013
DOI: 10.1136/jclinpath-2013-201879
|View full text |Cite
|
Sign up to set email alerts
|

Male hypercalciuric stone formers with low renal calcium reabsorption

Abstract: Hypercalciuric men reabsorbed proportionately less filtered calcium than normocalciuric men. Among hypercalciuric men, the risks for stones were higher in those with a high than a low filtered calcium load and presentation was earlier.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Traditionally, the biochemical basis for stone formation is supersaturation of urine with relation to the stone minerals, involving increased supersaturation of calcium and oxalate [ 2 ]. Recent data reported that as many as 30%–50% of male stone formers investigated in stone clinics have hypercalciuria, which in most cases is idiopathic [ 3 ]. To our knowledge, idiopathic hypercalciuria (IH) is the finality of the interaction between genetic background and environment.…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, the biochemical basis for stone formation is supersaturation of urine with relation to the stone minerals, involving increased supersaturation of calcium and oxalate [ 2 ]. Recent data reported that as many as 30%–50% of male stone formers investigated in stone clinics have hypercalciuria, which in most cases is idiopathic [ 3 ]. To our knowledge, idiopathic hypercalciuria (IH) is the finality of the interaction between genetic background and environment.…”
Section: Introductionmentioning
confidence: 99%
“…One of the initial steps for the formation of calcium oxalate stones is urine becoming supersaturated . Idiopathic hypercalciurie , low water intake, high protein or vitamin c intake and food rich in oxalate may lead to this . Another cause for urolithiasis in men is hyperuricosuria, which leads to acid urine and favours the formation of uric acid stones such as calcium oxalate stones .…”
Section: Resultsmentioning
confidence: 99%